2020
DOI: 10.1101/2020.05.31.20118679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delirium Incidence, Duration and Severity in Critically Ill Patients with COVID-19

Abstract: Background Delirium incidence, duration and severity in patients admitted to the intensive care unit (ICU) due to COVID-19 is not known. Methods We conducted an observational study at two large urban academic Level 1 trauma centers. Consecutive patients admitted to the ICU with a positive SARS-CoV-2 nasopharyngeal swab polymerase chain reaction test from March 1st, 2020 to April 27, 2020 were included. Individuals younger than 18 years of age, without any documented delirium assessments (CAM-ICU), or without… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The most frequent complication was delirium (36.70%), followed by coma, critical illness neuropathy, ischemic stroke, stupor, encephalopathy, seizures, cognitive deficit, and depression. The frequency of delirium is in line with current COVID-19 literature, in which it has ranged from 26.80 to 73.60% (34,36). Delirium was identified both in the acute and in the post-ICU phases during the severe acute respiratory syndrome (SARS) and Middle-East respiratory syndrome (MERS) epidemics, with a possible detrimental effect on length of stay (37).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The most frequent complication was delirium (36.70%), followed by coma, critical illness neuropathy, ischemic stroke, stupor, encephalopathy, seizures, cognitive deficit, and depression. The frequency of delirium is in line with current COVID-19 literature, in which it has ranged from 26.80 to 73.60% (34,36). Delirium was identified both in the acute and in the post-ICU phases during the severe acute respiratory syndrome (SARS) and Middle-East respiratory syndrome (MERS) epidemics, with a possible detrimental effect on length of stay (37).…”
Section: Discussionsupporting
confidence: 79%
“…A forest plot and a rank-hazard plot were provided for multivariate Cox regression. The rank-hazard plot is able to visualize the relationship between the relative hazard of variables entered in the multivariate Cox regression model(34). Logistic regression was performed to assess the risk factors associated with neurological complications.…”
mentioning
confidence: 99%
“…The most frequent complication was delirium (36.70%), followed by coma, critical illness neuropathy, ischemic stroke, stupor, encephalopathy, seizures, cognitive de cit, and depression. The frequency of delirium is in line with current COVID-19 literature, in which it has ranged from 26.80-73.60% (36,37). Delirium was identi ed both in the acute and in the post-ICU phases during the severe acute respiratory syndrome (SARS) and Middle-East respiratory syndrome (MERS) epidemics, with a possible detrimental effect on length of stay (38).…”
Section: Overall Populationsupporting
confidence: 76%
“…A forest plot and a rank-hazard plot were provided for multivariate regression. The rank-hazard plot is able to visualize the relationship between the relative hazard of variables entered in a multivariate Cox regression model [37]. Logistic regression was performed to assess the risk factors associated with neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have shown, COVID-19 patients have an estimated delirium prevalence rate of 73.6%. 20 Future studies should investigate underlying factors for the disproportionately higher number of cases and more severe cases of COVID-19 observed in ethnic minority groups.…”
Section: Observationsmentioning
confidence: 99%